Cardiovascular Risk Associated With Ibrutinib Use in Chronic Lymphocytic Leukemia: A Population-Based Cohort Study. Issue 31 (1st November 2021) - Abdel-Qadir, Husam; Sabrie, Nasruddin; Leong, Darryl; Pang, Andrea; Austin, Peter C.; Prica, Anca; Nanthakumar, Kumaraswamy; Calvillo-Argüelles, Oscar; Lee, Douglas S.; Thavendiranathan, Paaladinesh
Abstract : PURPOSE: Ibrutinib reduces mortality in chronic lymphocytic leukemia (CLL). It increases the risk of atrial fibrillation (AF) and bleeding and there are concerns about heart failure (HF) and central nervous system ischemic events. The magnitude of these risks remains poorly quantified. METHODS: Using linked administrative databases, we conducted a population-based cohort study of Ontario patients who were treated for CLL diagnosed between 2007 and 2019. We matched ibrutinib-treated patients with controls treated with chemotherapy but unexposed to ibrutinib on prior AF, age ≥ 66 years, anticoagulant exposure, and propensity for receiving ibrutinib. Study outcomes were AF-related health care contact, hospital-diagnosed bleeding, new diagnoses of HF, and hospitalizations for stroke and acute myocardial infarction (AMI). The cumulative incidence function was used to estimate absolute risks. We used cause-specific regression to study the association of ibrutinib with bleeding rates, while adjusting for anticoagulation as a time-varying covariate. RESULTS: We matched 778 pairs of ibrutinib-treated and unexposed patients with CLL (N = 1, 556). The 3-year incidence of AF-related health care contact was 22.7% (95% CI, 19.0 to 26.6) in ibrutinib-treated patients and 11.7% (95% CI, 9.0 to 14.8) in controls. The 3-year risk of hospital-diagnosed bleeding was 8.8% (95% CI, 6.5 to 11.7) in ibrutinib-treated patients and 3.1% (95% CI, 1.9 to 4.6) in controls. Ibrutinib-treated patients were more likely to start anticoagulation after the index date. After adjusting for anticoagulation as a time-varying covariate, ibrutinib remained positively associated with bleeding (HR, 2.58; 95% CI, 1.76 to 3.78). The 3-year risk of HF was 7.7% (95% CI, 5.4 to 10.6%) in ibrutinib-treated patients and 3.6% (95% CI, 2.2 to 5.4) in controls. There was no significant difference in the risk of ischemic stroke or AMI. CONCLUSION: Ibrutinib is associated with higher risk of AF, bleeding, and HF, but not AMI or stroke. Abstract :